2020
DOI: 10.1021/acs.jproteome.0c00160
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profiling of Fast Neutron-Induced Soybean Mutant Unveiled Pathways Associated with Increased Seed Protein Content

Abstract: Mutagenesis through fast neutron (FN) radiation of soybean resulted in a mutant with a 15% increase in seed protein content. A comparative genomic hybridization analysis confirmed that the mutant is lacking 24 genes located at chromosomes 5 and 10. A tandem mass tag-based proteomic profiling of the wild type and the FN mutant revealed 3,502 proteins, of which 206 proteins exhibited increased abundance and 214 proteins showed decreased abundance. Among the abundant proteins, basic 7S globulin increased fourfold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…The protein content of a soybean mutant induced by fast neutron (FN) irradiation was increased by 15%. Islam et al (2020) compared the difference in seed protein expression between the wild-type and FN-induced mutant and found that the level of basic 7S globulin in the mutant was fourfold higher than that in wild-type soybean seeds. This study provides a valuable germplasm resource for clarifying the molecular mechanism regulating the synthesis and degradation of soybean protein.…”
Section: Proteomicsmentioning
confidence: 99%
“…The protein content of a soybean mutant induced by fast neutron (FN) irradiation was increased by 15%. Islam et al (2020) compared the difference in seed protein expression between the wild-type and FN-induced mutant and found that the level of basic 7S globulin in the mutant was fourfold higher than that in wild-type soybean seeds. This study provides a valuable germplasm resource for clarifying the molecular mechanism regulating the synthesis and degradation of soybean protein.…”
Section: Proteomicsmentioning
confidence: 99%
“…R-studio was used for data visualization. The procedure used for metabolic mapping of omics data is described in refs , .…”
Section: Methodsmentioning
confidence: 99%
“…Genomic, transcriptomic, and proteomic analyses have been applied to some of the FN soybean mutants to characterize their seed composition. While some investigations were focused on root nodulation and other attributes of plant growth and response to the environment, , fewer studies have been performed on seed quality using metabolic profiling of soybean. Recently, an integrative transcriptomic and metabolomic approach has been directed toward improvement of seed quality in soybean. , …”
Section: Introductionmentioning
confidence: 99%
“…In the recent decade, fast neutron radiation-induced mutagenesis has been increasingly used due to its efficiency in rapidly generating a library of knockout genes [ 19 ]. Its ability to create multiple deletions ranging from 1 bp to 18 Mb has been valuable in delineating several biosynthesis pathways in important crops, such as raffinose family oligosaccharide synthesis [ 20 ] and seed protein synthesis in the soybean ( Glycine max ) [ 21 ]. To date, there are about 3200 radiation-induced plant varieties produced from 210 plant species cultivated in over 70 different countries [ 16 ].…”
Section: Mutation Breeding To Increase Plant Varietiesmentioning
confidence: 99%